Alterações químicas do solo irrigado com diluições de água produzida tratada em casa de vegetação - Rodrigues Filho, Ricardo André (Universidade Federal Rural do Semi-Árido, 2019)
Irrigation with produced water obtained from the oil extraction process can become an alternative to irrigated agriculture in semi-arid regions. However, the presence of salts, heavy metals and toxic substances in their composition must be taken into account, which may negatively impact the soil. The present work aimed to study the effects of the application of dilutions of wastewater of the treated oil in a Typic Rhodustults cultivated with sunflower. The treatments were based on the dilution of the produced water treated (AT) in well water (AP), being: 100AP0AT - 100% of AP and 0% of AT; 75AP25AT - 75% AP and 25% AT; 50AP50AT - 50% AP and 50% AT; 25AP75AT - 25% AP and 75% AT; and 0AP100AT - 0% AP and 100% AT. For this, 25 pots of 32L filled with Typic Rhodustults and cultivated with the sunflower (Heliantus annus) cultivar H-360. To fill the pots was used gravel (n ° zero) covering the bottom of the pots and covered by the soil. During the experimental period, water was collected to perform the characterization of the chemical attributes. After 90 days of application of the dilutions of AT in AP, soil samples were collected from 0 to 0.10 m and from 0.20 to 0.30 m from the pots to determine the following chemical attributes: pH, Na+, Ca+2, Mg+ 2 and electrical conductivity of the soil saturation extract (CEes). The data were submitted to analysis of variance, test of averages and orthogonal contrasts, using the statistical computer program SISVAR 5.6. The values pH, K+, and CO32 - presented higher values than those used for irrigation purposes, in addition, the dilutions also represent a moderate risk as regards the dispersion of the clays. Dilutions did not significantly alter the pH, CE Na+ and Ca2+ values of the soil, whereas 100AP0AT differed statistically from 0AP100AT only for Mg2+. The 75AP25AT dilution is the most recommended for irrigation purposes, since it minimized the chemical changes in the studied Typic Rhodustults.
Monografia
Keywords: Reúso; Água residuária; Petróleo; Irrigation; Wastewater; Oíl; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA